Climate change eco facts - Howell, Izzi (Howell, Izzi. Eco facts., 2020)
Introduces young readers to the causes of climate change and its effects around the world through a set of illustrated facts and statistics. Offers small steps that readers can take to stop climate change. Includes color photographs, a glossary, and further resources.